2002
DOI: 10.1016/s0893-133x(02)00329-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Technology of Clinical Trials and the Trials Model to Evaluate Newly Developed, Targeted Antidepressants

Abstract: Concern about disappointing results from recent multicenter trials of new antidepressants prompted several ACNP workshops on "improving the technology of clinical trials." The workshops focused on technical problems, such as patient screening, reliability of clinical ratings, and the role of the placebo control. They aimed to determine how to 27 , NO . 3 ducing adverse events, and lessening the complexity of dosing regimens. In addition, attention is currently focused on accelerating the onset of drug acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Items which occur in the disorder with lower mean severity were retained if they distinguished significantly between any primary BD syndromal states. Such items are essential in studies of behavioral domains of BD, definitions of diagnostic subtypes of BD and change with clinical state (10). Procedural guidelines and structured item queries were developed to facilitate ease of administration, inter‐rater reliability, and guard against biasing respondents to under or over report symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Items which occur in the disorder with lower mean severity were retained if they distinguished significantly between any primary BD syndromal states. Such items are essential in studies of behavioral domains of BD, definitions of diagnostic subtypes of BD and change with clinical state (10). Procedural guidelines and structured item queries were developed to facilitate ease of administration, inter‐rater reliability, and guard against biasing respondents to under or over report symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, earlier onset of response when compared with alternative treatment options has not always been observed [14,15], possibly because of methodological differences between studies. With speed of action becoming a central issue for pharmaceutical companies, specific methodological recommendations have been proposed for studies aimed at estimating onset of response [16,17]. According to Leon et al [16], key features include: (1) a prospective, operational definition of early onset of response; (2) frequent assessments of depression severity during the early phase of treatment; (3) strategies to minimise bias and heterogeneity of response, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Quitkin et al (1984a, b) and Quitkin and Stewart (1984) introduced a pattern analysis that identified persistent and non-persistent response and early and delayed onset of activity and the combination of these two, response level and onset patterns. Expectations of an early antidepressant effect from responder groups also changed the timing of data collection in clinical trials from weekly to 3 day or even more frequent intervals (for in-depth discussion of these approaches see reviews by Katz et al, 2002Katz et al, , 2004a). An analysis of the impact of effect measurement frequency on apparent drug AOT was conducted by Mallinckrodt et al (2006) who used a categorical repeated measures approach and a traditional assessment schedule, and found frequent estimates beneficial for data evaluation.…”
Section: Methods Used To Assess Activity Onset Time For Drugs In Clinmentioning
confidence: 99%